Cultural landscape: reclaiming the heritage of Minagkabau in Negeri Sembilan - Md Jani, Haza Hanurhaza; Mohd. Hussain, Mohd. Ramzi (2012)
Reclaiming cultural landscape is the idea of regaining the valuable heritage of human legacy that represents peoples’ identity and original culture of a group of people or place which cannot be replaced or regained after it has been destroyed. From Islamic point of view, cultural landscape presents the notion of revealing and sustaining the great diversity of the interactions between humans and their environment. Islam highlights the importance of human relationship with the environment and the associations involving the two assemblages have been emphasized repeatedly in the Qur’an. Due to its significance, this paper will be focusing on reclaiming cultural landscape of Minangkabau to ensure the heritage values, beliefs and traditions are being well preserved. -owadays, Minangkabau is losing its sense of identity which probably caused by its integration with other ethnicity in Malaysia. Since cultural landscape is considered as valuable heritage and it is irreplaceable, this research will be highlighting on the types of cultural landscape resources that influence the identity and character of Minangkabau ethnicity. The objectives of this paper are to emphasize the cultural landscape resources of Minangkabau ethnicity, consecutively to ensure people’s legacy is well preserved and to discover level of appreciation the original culture of Minangkabau among local people towards the notion of reclaiming the cultural landscape. This paper are presented in two sections; i) the theoretical framework and ii) methodology. The anticipated result will highlight the importance to reclaim cultural landscape as it is actually an approach to enrich the identity of Minangkabau ethnicity and sustain the heritage values. It is hoped that this paper will become a reference or guideline for future innovations and ideas regarding cultural landscape.